Pembuatan Aplikasi Perencanaan Jaringan Komputer Berbasis Android - Hartono, Nico; Noertjahyana, Agustinus; Gunawan, Ibnu (Jurnal Infra, 2015)
Technology is now growing rapidly in the world, namely smartphones, making us easy to do many things in daily life - today. The number of smartphones with Android Operating System helped us in many ways, including in the field of work. Along with the development of smartphone technology that requires a data connection, the computer network becomes a matter that needs to be developed. For the sake of ease of development of the network, the need for computer network design simulation software.This application helps in the manufacture of computer network that have personal computer components, switches and routers. IP on each component mounting aided by the function checks the correct format, subnet calculator that can help calculate IP quickly, and alsothe function of static routing on the router. This application is built using the Java programming language with the android his studio as an IDE.Results of the testing system, component in ease of application make some form of assistance filling of each object. The main canvas which has rescaling makes it easy to adapt the application with device that based on Android. The function of the switch which automatically takes the IP from each end of the interface. The search function is an automatic way data transmission and will identify existing static routing makes us also can map the data transmission device.